2008
DOI: 10.1152/ajpcell.00486.2007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of epithelial cell-specific expression and regulation of the human anion exchanger (pendrin) gene

Abstract: Pendrin, a Cl(-)/anion exchanger encoded by the gene PDS, is highly expressed in the kidney, thyroid, and inner ear epithelia and is essential for bicarbonate secretion, iodide accumulation, and endolymph ion balance, respectively. This study aimed to define promoter regulatory elements essential for renal, thyroid, and inner ear epithelial cell-specific expression of human PDS (hPDS) and to explore the effect of ambient pH and aldosterone on hPDS promoter activity. Endogenous pendrin mRNA and protein were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 59 publications
(97 reference statements)
4
45
2
Order By: Relevance
“…The strong reduction in pendrin expression, as well as its internalization observed in the B-intercalated cells of K + -depleted mice might be due to a fall in intracellular pH as a result of an increased exchange of K + out of the cell for H + into the cell. In line with these observations, previous studies showed that acidic pH decreases, whereas alkaline pH increases pendrin promoter activity in HEK293 cells [55]. Together, these observations support the concept that cellular acidosis leads to pendrin down-regulation that, in turn, participates in determining metabolic alkalosis in the setting of the chronic K + depletion.…”
Section: Discussionsupporting
confidence: 87%
“…The strong reduction in pendrin expression, as well as its internalization observed in the B-intercalated cells of K + -depleted mice might be due to a fall in intracellular pH as a result of an increased exchange of K + out of the cell for H + into the cell. In line with these observations, previous studies showed that acidic pH decreases, whereas alkaline pH increases pendrin promoter activity in HEK293 cells [55]. Together, these observations support the concept that cellular acidosis leads to pendrin down-regulation that, in turn, participates in determining metabolic alkalosis in the setting of the chronic K + depletion.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, it was not surprising to observe coordinated regulation of AE4 and pendrin in response to acidosis and alkalosis. Indeed, Foxi1 directly activates the AE4 promoter in vitro (14); in addition, low pH decreases and high pH increases human pendrin gene expression in transfected kidney cells (1). Acid loading for 24 -48 h causes a reduction in pendrin protein expression in the mouse kidney along with a shift of expression from the apical membrane to the cytosol (33), and these changes were reversed with alkali loading (33).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced luminal pendrin localization was observed in animals loaded with bicarbonate (203), given DOCA (196), or during chloride depletion (197), whereas several treatments altered total pendrin abundance in the kidney (57,67,139,192,203). Studies in various cell lines provided evidence for direct regulatory domains in the promoter region sensitive to intracellular pH and possibly to aldosterone (1). A fourth and indirect means of regulation may be changes in the number of pendrin expressing non-type A intercalated cells as observed in states of chronic metabolic acidosis or altered distal chloride delivery associated with a changed relative abundance of pendrin positive cells (67,192,203).…”
Section: Ae1mentioning
confidence: 99%